Pengaruh Stres Kerja dan Kompensasi Terhadap Turnover Karyawan pada CV. Eka Prima - Abdiana, Eka; Boyas, Jeziano; Qurratuaini, Nafia; Putrihadiningrum, Devika (Universitas Syiah Kuala, 2025)
The aim of the research is to identify and understand the influence of work stress and compensation on turnover. This research applies a quantitative approach with a population of 119 employees. The sampling technique used was purposive sampling, with a total of 57 respondents. Data was collected through a questionnaire distributed using Google Form. Data analysis was carried out using the Partial Least Square (PLS) method using SmartPLS 4.0 software. In PLS there are two types of models explained, namely the outer model and the inner model. The research results show that work stress has a negative influence on turnover, while compensation has a positive influence on turnover. Apart from that, simultaneously, work stress and compensation have a positive effect on turnover